Keefektifan Model Problem Based Learning Terhadap Hasil Belajar IPA Siswa Kelas IV SD Negeri 68 Palembang - Yansah, Feri; Hermansah, Bambang; Marleni, Marleni (Indonesian Research Journal on Education, 2023)
The goal to be achieved in this study is to determine the effectiveness of the Problem Based Learning model on the science learning outcomes of fourth grade students of SD Negeri 68 Palembang. This research method uses an experimental method with a True Experimental Design type of research and the research design is a Posttest-Only control design. The population of this study were all fourth grade students of SD Negeri 68 Palembang, while the research sample was 27 students of class IV A as the experimental class and 30 students of class IV B as the control class. Data collection techniques that researchers use are test, observation, and documentation techniques, while data analysis techniques uset-test. Based on the results of the study, it was found that the average science learning outcomes in fourth grade students at SD Negeri 68 Palembang in the experimental class after being given the Problem Based Learning model was 81.13, while the control class average was 70.19. Thus, there was an increase in science learning outcomes for fourth grade students at SD Negeri 68 Palembang after being given the Problem Based Learning model. Based on the results of hypothesis testing, it was found that the value oftcount ttable or 3.442 > 1.673034. Thus, it can be concluded that Ho is rejected and Ha is accepted or the use of the Problem Based Learning model on science learning outcomes for fourth grade students at SD Negeri 68 Palembang is effective.